Photochemical Action Plots Map Orthogonal Reactivity in Photochemical Release Systems - Rita T. Michenfelder; Fred Pashley‐Johnson; Viktor Guschin; Laura Delafresnaye; Vinh X. Truong; Hans‐Achim Wagenknecht; Christopher Barner‐Kowollik (Advanced Science, 2024)
Abstract The wavelength‐by‐wavelength resolved photoreactivity of two photo‐caged carboxylic acids, i. e. 7‐(diethylamino)‐coumarin‐ and 3‐perylene‐modified substrates, is investigated via photochemical action plots. The observed wavelength‐dependent reactivity of the chromophores is contrasted with their absorption profile. The photochemical action plots reveal a remarkable mismatch between the maximum reactivity and the absorbance. Through the action plot data, the study is able to uncover photochemical reactivity maxima at longer and shorter wavelengths, where the molar absorptivity of the chromophores is strongly reduced. Finally, the laser experiments are translated to light emitting diode (LED) irradiation and show efficient visible‐light‐induced release in a near fully wavelength‐orthogonal, sequence‐independent fashion (λLED1 = 405 nm, λLED2 = 505 nm) with both chromophores in the same reaction solution. The herein pioneered wavelength orthogonal release systems open an avenue for releasing two different molecular cargos with visible light in a fully orthogonal fashion.